The Enforcement of MUI Fatwa Number 1 of 2003 concerning Copyright for Merchants Selling Pirated VCD and DVD in Manado City - Willya, Evra; Maronrong, Ahmad B. Bintang; Mokodenseho, Sabil (Al-Ahkam, 2021)
This article aims to determine the enforcement of the MUI Fatwa Number 1 of 2003 concerning Copyrights for Muslim merchants selling pirated VCDs and DVDs in Market 45, Manado City. A qualitative method with observation, interview, and documentation techniques was used to analyze the data. Of the six Muslim traders interviewed, the results showed that the MUI fatwa enforcement was ineffective due to the lack of socialization and evaluation of merchants. Also, the merchants did not stop selling pirated products because they lacked religious understanding and awareness and lived below the poverty line. At the same time, the authors' economic rights become a barrier to the public in accessing the product because it is valued beyond the ability of consumers. This study suggests that the MUI ought to pay attention to the economic balance between the authors' economic rights and the public, such as merchants.